A Science-Based Ecosocialist Strategy for Climate Security - David Schwartzman (Journal of World-Systems Research)
The natural, physical, and informational sciences—in particular, climatology, ecology, biogeochemistry, and thermodynamics—which along with the wisdom derived from the experience of thousands of years of indigenous peoples’ agriculture and culture should inform an effective global plan to prevent future climate catastrophes much worse than now witnessed which will very likely occur if the 1.5°C warming limit is exceeded in the next few decades. Strategy is imperative to guide transnational political struggle, to first defeat fossil capital while creating a Global Green New Deal (GGND) confronting the growing threat of climate catastrophes. Degrowth has been promoted as a program for climate security, but a major problem is its grounding in Georgescu-Roegen’s fallacious entropy concept with regard to energy supplies to society. Degrowthers call for a global reduction in energy. However, sufficient levels of renewable energy likely greater than the present global energy consumption level will eliminate energy poverty while having the capacity for climate mitigation and adaptation with a phase out of extractive industries. Organizing for a GGND must start now with the recognition of the role of green capital at least in its first stage, both for implementation of an ever-growing renewable energy infrastructure replacing fossil fuel, as well as a potential ally in defeating the agenda of militarized fossil capital. At the same time, green capital must be challenged to insure environmental, worker and community protection. The GGND can potentially develop in an increasingly ecosocialist direction, culminating with end of reproduction of capital on the planet.